(untitled) (Journal of Philosophy Culture and Political Science, 2019)
In article the problem of comparison of concept of sense in B. Russell, G. Frege’s analytical philosophy, is considered by J. Watson, E.Gusserle and L.Vitgenstein. Here concepts can keep the objective value and without extensional, no less than offers without referential instructions can have objectively pro-item contents still. Such separation of concept of value from concept of sense has far-reaching results in philosophy of language and sense of the XX century.